1936
DOI: 10.1063/1.1745374
|View full text |Cite
|
Sign up to set email alerts
|

The Dielectric Constant of Air at Radiofrequencies

Abstract: The heterodyne beat frequency method of determining dielectric constants has been applied to the measurement of the dielectric constant of air with an applied frequency of field of 900,000 cycles per second. Radio broadcast signals, stripped of modulation, were used as sources of alternating current of constant high frequency. An electron coupled oscillator was used in the circuit containing the test condenser. Both sources of high frequency were isolated from the detector through buffer stages of amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…As source function a time dependent surface charge located [39,40] at the hypothetical crack surface and the time dependent generation of the respective electric field is used. The electric potential V is calculated by solving a current conservation problem based on Ohm's law:…”
Section: Modellingmentioning
confidence: 99%
“…As source function a time dependent surface charge located [39,40] at the hypothetical crack surface and the time dependent generation of the respective electric field is used. The electric potential V is calculated by solving a current conservation problem based on Ohm's law:…”
Section: Modellingmentioning
confidence: 99%
“…This is validated by the phase angle plots which clearly show a shift in phase at fracture in the low frequency spectra. When the phase angle becomes zero, this implies that both the voltage and current are at the same phase and the material doesn't exhibit a capacitive nature, which was observed in normalized permittivity plots shown in Figure 10 [26]. When the same properties as neat resin were used, it was observed that there was no significant variation in the predicted dielectric response, and whatever variations were observed were due to changes in shape (geometry) as shown in Figure 11.…”
Section: Vadlamudi Et Almentioning
confidence: 63%
“…This measurement can then be looked on as an air reference calibration. According to the literature, the relative permittivity of air under normal condition is 1.00058986 ± 0.00000050 [14] and the loss factor is assumed to be small but dependent on humidity. However, for the present accuracy requirements, the relative permittivity of air can be set to unity with no losses.…”
Section: Air Reference Methodsmentioning
confidence: 99%